Hydration and microhardness of mineral trioxide aggregate depending on ratio between di‐ and tricalcium silicates. Issue 3 (18th November 2021) - Kim, Yurian; Lee, Se Woong; Rho, Hyung Tay; Kim, Sang‐il
Abstract: Tricalcium silicate (C3 S) and dicalcium silicate (C2 S) are the main components related with the hydration process of mineral trioxide aggregates (MTAs) for endodontic materials. In this study, we investigate the influence of different ratios of C3 S and C2 S in a series of MTA samples with (100‐ x )C3 S‐ x C2 S‐18ZrO2 ( x = 0, 10, 15, 34, and 100) on their physical and chemical characteristics, hydration process, and microhardness properties. The chemical compositional properties of different samples are measured using X‐ray diffraction, X‐ray photoelectron spectrometry, and scanning electron microscopy. The physical and microhardness properties are also investigated after the standard hydration process (ISO 6876:2021). Generally, the sample with higher C3 S ratio induces the faster hydration, which results in decreased fluidity as well as shorter working and setting times. The microhardness generally decreases with larger C3 S ratio.